PELAKSANAAN PROGRAM TOL LAUT PT PELAYARAN NASIONAL INDONESIA - Devi Destiani Andilas; Liana Angelia Yanggana (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2017)
Sea Highway is one of the Indonesian government’s programs that aimed at reducing price disparities that occur between the West Indonesia (especially Java) and the East Indonesia with the use of sea transport. The government appointed PT Pelayaran Nasional Indonesia (PELNI) to run the Sea Highway program started from November 2015 by providing ships with the scheduled system from the western of Indonesia to the eastern of Indonesia and vice versa. This study was held to analyze the implementation of the PT PELNI’s Sea Highway program especially in aspects of routes, frequency, and volume of the transported vessel, which only restricted from Surabaya to Eastern Indonesia’s route. The results show that the route and frequency of Sea Highway are running consistently, while the volume is increasing if it’s compare with the first time it started. The 3 aspects of Sea Highway (route, frequency, volume) influence each other; therefore it’s suggested for government to improve the efficiency of those three aspects so the Sea Highway’s purpose in reducing price disparities in Eastern Indonesia can be achieved maximally. Moreover, the research results also show that Sea Highway program never takes the private shipping company’s commercial route.